2010
DOI: 10.1002/lary.21298
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Cardiovascular Risk Factors and Incident Hearing Loss in Men

Abstract: Objective-Hearing loss is the most common sensory disorder in the US, afflicting over 36 million people. Cardiovascular risk factors have been associated with hearing loss risk in crosssectional studies, but prospective data are currently lacking.Methods-We prospectively evaluated the association between diagnosis of hypertension, diabetes mellitus, hypercholesterolemia, smoking and body mass index (BMI) and incidence of hearing loss. Participants were 26,917 men in the Health Professionals Follow-up Study, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 23 publications
3
52
4
Order By: Relevance
“…Some of the tonal audiometry studies demonstrate that AH patients present slowly progressive symmetrical sensorineural highfrequency hearing loss [5][6][7][8]. However, other authors deny worse cochlear function in patients with hypertension [19,20] or regard hypertension as a weak risk factor [21]. Interestingly, Agrawal et al [21] have shown that hypertensive patients present hearing loss only in the range of 1 kHz.…”
Section: Discussionmentioning
confidence: 95%
“…Some of the tonal audiometry studies demonstrate that AH patients present slowly progressive symmetrical sensorineural highfrequency hearing loss [5][6][7][8]. However, other authors deny worse cochlear function in patients with hypertension [19,20] or regard hypertension as a weak risk factor [21]. Interestingly, Agrawal et al [21] have shown that hypertensive patients present hearing loss only in the range of 1 kHz.…”
Section: Discussionmentioning
confidence: 95%
“…A study of adolescents aged 12-19 years found a relationship between obesity and higher hearing thresholds at all frequencies [6]. Other studies, however, have found no association between obesity and increasing risk of hearing loss [7]. Thus, the relationship between obesity and hearing may be dependent on the age and gender of the subjects, the number of subjects analyzed, and study method.…”
Section: Introductionmentioning
confidence: 96%
“…In a recent meta‐analysis of 23 studies on SSHL, the suspected etiologies detected were infections (12.8%), otologic diseases (4.7%), trauma (4.2%), vascular and hematological problems (2.8%), and neoplastic diseases (2.3%) . Although SSHL is currently assumed as multicausal, recent studies have proposed vascular occlusion as the main process responsible for neurosensorial damage in the inner ear . In some aspects, the clinical presentation of unilateral SSHL is comparable to an ischemic vascular disease such as myocardial infarction, transient ischemic attacks, or amaurosis fugax .…”
Section: Introductionmentioning
confidence: 99%